PROBLEMATIKA GURU DALAM PEMBELAJARAN KALIGRAFI DI SEKOLAH DASAR - Muhammadiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
As one of the arts in Islam, calligraphy is often considered difficult to learn, even though calligraphy is very important to preserve. The purpose of this study is to further explore the problems or problems experienced by teachers at MI NU 2 Tembilahan. The research method used was qualitative with one informant, namely a calligraphy teacher. The instruments used to obtain data are interviews and documentation. Data analysis techniques using Miles and Hubberman are data reduction, data presentation, and conclusion drawn. The results of the study show that there are three problems experienced by teachers in learning calligraphy, including, lack of student interest, difficulty in finding calligraphers who are willing to teach, lack of facilities that support calligraphy learning. The solution that can be done is to give students appreciation, use social media and the internet, and simplify or make the most of existing facilities.